OPTIMALISASI PERAN GENERASI MUDA PAPUA DALAM PEMBANGUNAN BERKELANJUTAN DI DISTRIK MAKBON KABUPATEN SORONG - Ismed Kelibay; Niny Jeni Maipauw; Kamaluddin Kamaluddin; Muhammad Arifin Abdul Kadir; Rusdi Rusdi (Universitas Mataram, 2022)
The younger generation has a very important role as actors and movers in society and is an effort to raise public awareness regarding sustainable development in Indonesia. The purpose of this activity is to optimize the role of the young generation of Papua, especially in the Makbon District, Sorong Regency, in providing knowledge to the community about the importance of sustainable development and being able to implement their potential. The method used in carrying out this activity refers to the analysis of the situation in the local community. In addition, the implementation of this community service activity is also divided into three stages including (1) Preparation, (2) Implementation, and (3) Evaluation. The results obtained through this activity, the youth and the community as participants who attended the socialization activities have given a positive response because many of the participants did not understand the concept of sustainable development. The discussion became even more interesting because many participants began to actively ask about the forms of youth and community involvement in the development process in Makbon District, Sorong Regency. from these results it can be concluded, the community service activities carried out have provided an overview of knowledge and new insights regarding how to optimize the role of the younger generation in sustainable development in Makbon District, Sorong Regency.